Microstructure and dielectric properties of (1-x)SrFe0.5Nb0.5O3-xBaTiO3ceramics - Thanatep Phatungthane (2018)
© 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved. (1-x)SrFe0.5Nb0.5O3-xBaTiO3((1-x)SFN-xBT) powders with x=0.00-0.50 were synthesized via a molten-salt synthesis process. All x<0.50 calcined powders exhibited pure phase perovskite after a relatively low calcination temperature of 800 °C. Ceramics of (1-x)SFN-xBT were then fabricated from the calcined powders. Increasing BT inhibited grain growth, but produced an improvement in dielectric constant. Very high dielectric constants (εr~2.96×105at 1 kHz and 351 °C) were recorded for the x=0.25 ceramics. All ceramics displayed a strong frequency dependent dielectric, especially for the x=0.25 ceramics. The dielectric constant behaviour of the studied ceramics was related to the Maxwell-Wagner polarization mechanism. In addition, the x=0.25 ceramics exhibited a very high relative dielectric tunability (nr~76%) at room temperature.